FKRP-related limb-girdle muscular dystrophy R9 in Norway – Studies of epidemiology, natural history, and relationships with health-related quality of life and sleep - Jensen, Synnøve (UiT The Arctic University of Norway, 2024)
Background/aims: Limb-girdle muscular dystrophy R9 (LGMDR9) is a rare autosomal recessive muscle disease caused by mutations in the fukutin-related protein gene, FKRP. The prevalence is higher in northern European populations, where it is closely associated with the FKRP c.826CA allele. This work aims to study the epidemiology of LGMDR9 in Norway, natural history, and relationships with health-related quality of life (HRQoL) and sleep in the Norwegian LGMDR9 population. Methods: Subjects with genetically confirmed LGMDR9 were identified through Norwegian hospital departments and invited to “The Norwegian LGMDR9 cohort study”. A questionnaire and patient notes were collected from consenting persons. Adults were also invited to the University hospital of North Norway for a battery of tests, and to postal surveys on HRQoL, fatigue, and sleep. The HRQoLs were administered three times during a 14-month period. Results: A total of 153 subjects were identified, of whom 88% were c.826C>A homozygotes. The county-level prevalence ranged 0.63-8.32/100,000 and was highest in Northern and Central Norway and lowest in south-west Norway. Among c.826C>A homozygotes, females showed an increased cumulative probability of wheelchair dependency and need for Positive Airway Pressure (PAP) therapy, whereas males were more predisposed to cardiomyopathy. Females reported higher LGMDR9-related burden than males. Both physical, social, and mental HRQoL were impaired. During the 14-month period, perceived muscle weakness and LGMR9 burden worsened in c.826C>A homozygotes. Burden was related to perceived muscle weakness and fatigue. Fatigue was prevalent (40%), associated with insomnia, and correlated with level of mental distress, myalgia, and inspiratory weakness. Insomnia was prevalent both among subjects with and without PAP therapy and was negatively correlated with mental HRQoL. Among subjects without PAP therapy, undiagnosed sleep apnea was frequent, and the apnea-hypopnea index correlated with advancing age and cardiac ...